2016
DOI: 10.3934/publichealth.2016.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Magnesium Sulfate Tocolysis in Preterm Labor (PTL)

Abstract: The U.S. Food and Drug Administration issued a drug safety communication on 05/30/2013 recommending “against prolonged use of magnesium sulfate to stop preterm labor (PTL) due to bone changes in exposed babies.” In September of 2013, The American Congress of Obstetrics and Gynecologists issued Committee Opinion No. 573 “ Magnesium Sulfate Use in Obstetrics” , which supports the short term use of MgSO4 to prolong pregnancy (up to 48 hrs.) to allow for the administration of antenatal corticosteroids.” Are these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…The findings of this review are reassuring and can be considered in conjunction with those from relevant reviews demonstrating a clear benefit of antenatal magnesium sulphate [1,2,4], and current international clinical practice guideline recommendations [3,7]. Our review findings of possible adverse outcomes with long-term, high-dose use for tocolysis have implications for settings with continued use for this indication [8] in spite of the absence of benefit shown in systematic reviews and international guidance [7–9].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The findings of this review are reassuring and can be considered in conjunction with those from relevant reviews demonstrating a clear benefit of antenatal magnesium sulphate [1,2,4], and current international clinical practice guideline recommendations [3,7]. Our review findings of possible adverse outcomes with long-term, high-dose use for tocolysis have implications for settings with continued use for this indication [8] in spite of the absence of benefit shown in systematic reviews and international guidance [7–9].…”
Section: Discussionmentioning
confidence: 61%
“…Systematic reviews and clinical practice guidelines support its use when given for maternal neuroprotection in pre-eclampsia or eclampsia [1–3] and for neuroprotection of the fetus in women at risk of preterm birth (for cerebral palsy prevention) [4–7]. Despite continued use in some countries [8], available evidence does not support its role in preventing preterm birth in women with, or following, threatened preterm labour (for tocolysis) [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In babies bone demineralization seen which was reversible. 9 Mahajan et al showed successful tocolysis in 82% cases and 66% cases with magnesium sulphate and isoxsuprine respectively. Magnesium sulphate was able to maintain successful tocolysis for 7 days in 74% cases as compared to 50% in patients receiving isoxsupine.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, tocolytic drugs are the main option for the treatment of preterm birth. Unfortunately, they have been frequently associated with low efficacy and adverse reactions (Clouqueur et al, 2015;Elliott, Morrison, & Bofill, 2016;Guden et al, 2016). For that reason, the development of new drugs and/or the discovery of medicinal plants for the treatment of PTB is an area of growing interest.…”
Section: Discussionmentioning
confidence: 99%